The hidden burden of adolescent pregnancies in rural Sri Lanka; findings of the Rajarata Pregnancy Cohort - Thilini Chanchala Agampodi; Nuwan Darshana Wickramasinghe; Hemali Gayathri Jayakodi; Gayani Shashikala Amarasinghe; Janith Niwanthaka Warnasekara; Ayesh Umeshana Hettiarachchi; Imasha Upulini Jayasinghe; Iresha Sandamali Koralegedara; Sajaan Praveena Gunarathne; Dulani Kanchana Somasiri; Suneth Buddhika Agampodi (BMC, 2021)
Abstract Background Adolescent fertility is a main indicator of the Sustainable Developmental Goal (SGD) three. Although Sri Lanka is exemplary in maternal health, the utilization of Sexual and Reproductive Health services (SRH) by adolescents is less documented. We describe the hidden burden, associated biological and psychosocial factors and utilization patterns of pre-conceptional services among pregnant adolescents in rural Sri Lanka. Methods The study is based on the baseline assessment of the Rajarata Pregnancy Cohort (RaPCo) in Anuradhapura. Pregnant women newly registered from July to September 2019 were recruited to the study. The period of gestation was confirmed during the second follow-up visit (around 25-28 weeks of gestation) using ultra sound scan data. A history, clinical examination, anthropometric measurements, blood investigations were conducted. Mental health status was assessed using the Edinburgh Postpartum Depression Scale (EPDS). Results Baseline data on gestation was completed by 3,367 pregnant women. Of them, 254 (7.5%) were adolescent pregnancies. Among the primigravida mothers (n = 1037), 22.4% (n = 233) were adolescent pregnancies. Maternal and paternal low education level, being unmarried, and less time since marriage were statistically significant factors associated with adolescent pregnancies (p < 0.05). Contraceptive usage before pregnancy, utilization of pre-conceptional health care services, planning pregnancy and consuming folic acid was significantly low among adolescents (p < 0.001). They also had low body mass index (p < 0.001) and low hemoglobin levels (p = 0.03). Adolescent mothers were less happy of being pregnant (p = 0.006) and had significantly higher levels of anxiety (p = 0.009). Conclusion One fifth of women in their first pregnancy in this study population are adolescents. Nulli-parous adolescents exert poor social stability and compromised physical and mental health effects. The underutilization and/or unavailability of SRH services is clearly associated with adolescent pregnancies.